On the Design of a High Band-Ratio Mid-Section Crossed Dual-Band Branch-Line Coupler With Arbitrary Power Division Ratio Using Perturbation Factor - Ahammad; Asif Iftekhar Omi; Mohammad H. Maktoomi; Mohammad A. Maktoomi; Praveen K. Sekhar (IEEE Access)
This article presents a Mid-section crossed dual-band Branch-Line Coupler (MBLC) with port extensions, along with a new design methodology for both complex and conventional structured branch-Line couplers. The proposed MBLC structure features a conventional branch-line coupler with a crossed line at the center, as well as an L-section impedance matching network at all four ports, which facilitates analysis and design. A comprehensive theoretical analysis is performed to derive closed-form design equations for determining the design parameters of the coupler using a perturbation factor. The analysis demonstrates that the proposed MBLC can support a wide band ratio of up to 11, indicating a broad operating frequency range. To evaluate the performance of the proposed MBLC, two prototypes were fabricated on a 62 mil Rogers 4003C substrate, operating at 1 GHz and 2 GHz for equal and unequal power division cases. The simulated and measured results for both prototypes showed an excellent match, with a magnitude imbalance of less than 4% and a phase imbalance of less than 2%. Overall, the proposed MBLC with port extensions in conjunction with the new design methodology demonstrated promising results for the development of efficient and effective dual-band branch-line couplers.